The Real History of Protestantism: Thomas Carlyle and the Spirit of Reformation. Issue 1 (1st April 2014) - Morrow, John
Abstract: Carlyle regarded the Reformation as a seminal event in the history of modern Europe, the starting point of an ongoing stage in human development. Reformation Protestantism gave birth to a more general and pervasive spirit of 'reformation' that Carlyle identified with the moral destiny of all individuals and communities. These qualities were epitomized by heroic figures such as Luther and Cromwell but they were also embedded in cultures that responded productively to the ongoing challenge of reformation. Having traced the history of the ethos of reformation through English Puritanism and in the commitment to transformative action or 'work' that gave rise to Britain's emergence as a leading industrial and imperial power, Carlyle brought this reinvention of the Reformation to bear in his critique of the counter-reforming tendencies in early Victorian society that he saw as posing a profound threat to it.